1971
DOI: 10.1002/1097-0142(1971)28:5<1087::aid-cncr2820280502>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced sarcoma of bone

Abstract: During the period 1931 to 1970, 50 cases of radiation‐induced osteogenic sarcoma were seen at the Memorial and James Ewing Hospitals. Twenty‐two of these cases had previously been described; the present paper adds an additional 28 cases to the existing series and reviews those factors related to the development of neoplastic changes. In 35 patients, there was evidence of preexisting bone pathology in the form of benign osseous growths. Fifteen patients had soft‐part and visceral neoplasms, such as retinoblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
1
7

Year Published

1977
1977
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(187 citation statements)
references
References 18 publications
6
173
1
7
Order By: Relevance
“…[18][19][20][21]29 In our study, we used the most common latency criteria of 3 to 4 years as reported by Arlen et al 21 The median latency in our series, 9.3 years, was consistent with data from other studies, in which the median latency ranges from 7.6 years to 22 years. [3][4][5][6][7][8][9][10][11]29 The shorter period of 7.6 years reported by Kuttesch et al 26 may be explained by the younger age of their patients.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Alsupporting
confidence: 79%
See 1 more Smart Citation
“…[18][19][20][21]29 In our study, we used the most common latency criteria of 3 to 4 years as reported by Arlen et al 21 The median latency in our series, 9.3 years, was consistent with data from other studies, in which the median latency ranges from 7.6 years to 22 years. [3][4][5][6][7][8][9][10][11]29 The shorter period of 7.6 years reported by Kuttesch et al 26 may be explained by the younger age of their patients.…”
Section: Radiation-induced Sarcoma In Npc/xi Et Alsupporting
confidence: 79%
“…Eligibility for this retrospective study was based on the criteria for RIS published by Cahan et al 20 as modified by Arlen et al 21 : 1) a prior history of RT, 2) the occurrence of sarcoma within the previously irradiated field, 3) histologic confirmation of the sarcomatous nature of the postirradiation lesion, and 4) a latency between irradiation and a second primary sarcoma of at least 3 years. After reviewing the institutional electronic medical records, 53 patients who developed RIS and fulfilled these criteria were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The defi nition criteria of radiation-induced sarcomas were proposed by Cahan et al and modifi ed by Arlen et al and include (1) treatment with therapeutic irradiation at least 3 years prior to the development of sarcoma, (2) a sarcoma arising within the fi eld of previous therapeutic irradiation, and (3) differing histology between the sarcoma and the primary tumor that required radiotherapy (Cahan et al 1948 ;Arlen et al 1971 ). The latency period between radiation exposure and sarcoma formation is the major controversial criterion and has been modifi ed by several investigators.…”
Section: Malignant Tumorsmentioning
confidence: 99%
“…The most common histological subtypes are osteosarcoma and malignant fi brous histiocytoma, although other histologies (e.g., angiosarcoma, rhabdomyosarcoma) can occur. It is estimated that the risk of developing osteosarcoma in irradiated bone is 0.03-0.8 % (Kalra et al 2007 ;Huvos et al 1985 ;Koshurnikova et al 2000 ;Arlen et al 1971 ;Mark et al 1994 ;Enneking et al 1980 ;Kaplan and Meier 1958 ;Nakanishi et al 1998 ;Mertens et al 2000 ).…”
Section: Malignant Tumorsmentioning
confidence: 99%
“…в 1971 г. [5]. К ним авторы отнесли следующие критерии: лучевая терапия проведена не менее чем за три года до развития саркомы; опухоль возникает в пределах зоны ранее облученных тканей; разная гистологическая структура опухолей.…”
unclassified